Molecular epidemiology of staphylococcus aureus isolated from the patients, personnel and hospital environments in Sanandaj (Iran) - Mohammadi Talvar, Hadi; Ramazanzadeh, Rashid; Mirzaii, Mehdi; Hasheminasab, Seyed Sajjad (International Journal of Scientific World, 2017)
The aim of this study was to determine the prevalence and characteristics of methicillin-resistant Staphylococcus aureus (MRSA) isolates from the patients, personnel and environments of a hospital in Sanandaj. During this study, 30 MRSA isolates were collected and analyzed with using spa typing method. Out of the 30 S. aureus isolates, 28 (93.33%) was methicillin resistant (MRSA),16spastypesp(t030,t711,t002,t1556,5t325,t267,t1358,t230,t2422,t969,t1814,t037,t300,t044,t180,andat5598)9wereefounduin differentewardsrof thethospital.aTheTmostofrequentewereet0300(17.27%),%t7117(13.73%).%OUrOdataademonstratedtthaththetoverall, resistancescto erythromycin, igentamycin, iandaciprofloxacin, iwereemostofrequente (87.5,.81.25,2anda62.52respectively).y).